2022
DOI: 10.1002/er.8287
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the strategies to attain the best performance of all inorganic lead‐free perovskite solar cells: Theoretical insights

Abstract: Summary Within a decade of their existence, the potential of Perovskite solar cells (PSCs) has been recognized by the research community. To date, the highest power conversion efficiency (PCE) attained by PSCs has touched the 25.8% mark. However, most of the leading PSCs have incorporation of toxic lead (Pb), posing a barrier on the market acceptability of these cells. Inorganic lead‐free PSCs are being explored extensively as clean and green energy sources. By bridging the performance gap and stability issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…After the optimized level, for positive CBO conditions, the spike structure is formed, which acts as a barrier to the photogenerated electrons, hindering the carrier transportation and extraction. [ 20,34,35 ] Figure 2 depicts different levels of CBOs and VBOs of simulated PSCs, analyzed in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the optimized level, for positive CBO conditions, the spike structure is formed, which acts as a barrier to the photogenerated electrons, hindering the carrier transportation and extraction. [ 20,34,35 ] Figure 2 depicts different levels of CBOs and VBOs of simulated PSCs, analyzed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…After the optimized level, for positive CBO conditions, the spike structure is formed, which acts as a barrier to the photogenerated electrons, hindering the carrier transportation and extraction. [20,34,35] In this section, the CBOs are varied by keeping VBO at a constant level and at an interface defect density of 1E16 cm À3 . The activation energy (E a ) is defined as the minimum amount of extra energy required by a reacting molecule to get converted into a product.…”
Section: Role Of Positive and Negative Conduction Band Offset In Etl/...mentioning
confidence: 99%
“…The modification of doping levels causes a change in both acceptor and donor carrier concentrations (N a and N d ), subsequently, elevating the overall carrier concentration as well as enhancing the device's conductivity. The built-in potential relies on the acceptor and donor carrier concentrations, dictated by the following equation (7) [64].…”
Section: Shallow Uniform Donor Density Optimizationmentioning
confidence: 99%
“…The incidence of light on the LHL highlights the pivotal role of the built-in electric field in producing and separating charge carriers. Enhanced performance of the cell corresponds directly with a stronger built-in electric field within the LHL, facilitating the efficacious extraction of charge carriers from the LHL to the contacts of charge collections [64]. Introducing dopants into the transport layer amplifies the conductivity, thereby augmenting the built-in electric field.…”
Section: Shallow Uniform Donor Density Optimizationmentioning
confidence: 99%
“…The detailed material parameters utilized in device simulation. [39][40][41][42][43][44] Parameters/Material HTM layer (Spiro-OMeTAD) Absorption coefficient [cm À1 ] 1 0 3 10 3 10 5 10 3 10 3 concentration (electron density) in the native oxide layer does not cause any band bending or impact on efficiency as the native layer is of a high bandgap and thin layer (%5 nm). We simulated all crucial parameters of the oxide layer (such as thickness, electron affinity, and carrier density), impacting the device performance, and observed that the device efficiency does not strongly dependent on the oxide layer.…”
Section: Native Oxide Simulationmentioning
confidence: 99%